Efficiency in construction process - Muhammad Muslim , Ramle (2012)
Construction industry currently is facing with a lot of problems mainly associated to its inefficient work process. This phenomenon has been manifested by frequent news and critics about project delay and inferior quality. Therefore there is an urgent need for construction industry to improve this situation. Many efforts have been done to improve the performance of the construction industry reputation such as using alternative procurement system, adoption of tools and management philosophy from other industry and using to new technological advancement such as the used of modular construction in Malaysia. In view to these problems face by the industry, this study has been undertaken with the aim to determine the strategies to improve the efficiency in construction process. The methodologies adopted for this study are the interview with expert panels and the distribution Of questionnaires survey. The findings from this study confirmed that the construction industry particularly in Malaysia need to be improved with regards to its efficiency. There are also a lot of problems associated to construction such as poor site management, redundancy of activities, project delay and lack of focus to customer/end users' requirement. The study also determined that the main strategies currently promoted to achieve the improvement are by using Industrialized Building System (IBS). Many organizations also integrate the quality management system such as ISO 9001 and Total Quality Management System (TQM) in their business process. The used of management tools and philosophies from other industry is not a popular strategy.